The benefits of very low earth orbit for earth observation missions. (August 2020) - Crisp, N.H.; Roberts, P.C.E.; Livadiotti, S.; Oiko, V.T.A.; Edmondson, S.; Haigh, S.J.; Huyton, C.; Sinpetru, L.A.; Smith, K.L.; Worrall, S.D.; Becedas, J.; Domínguez, R.M.; et al.
Abstract: Very low Earth orbits (VLEO), typically classified as orbits below approximately 450 km in altitude, have the potential to provide significant benefits to spacecraft over those that operate in higher altitude orbits. This paper provides a comprehensive review and analysis of these benefits to spacecraft operations in VLEO, with parametric investigation of those which apply specifically to Earth observation missions. The most significant benefit for optical imaging systems is that a reduction in orbital altitude improves spatial resolution for a similar payload specification. Alternatively mass and volume savings can be made whilst maintaining a given performance. Similarly, for radar and lidar systems, the signal-to-noise ratio can be improved. Additional benefits include improved geospatial position accuracy, improvements in communications link-budgets, and greater launch vehicle insertion capability. The collision risk with orbital debris and radiation environment can be shown to be improved in lower altitude orbits, whilst compliance with IADC guidelines for spacecraft post-mission lifetime and deorbit is also assisted. Finally, VLEO offers opportunities to exploit novel atmosphere-breathing electric propulsion systems and aerodynamic attitude and orbit control methods. However, key challenges associated with our understanding of the lower thermosphere, aerodynamic drag, the requirement to provide a meaningful orbital lifetime whilst minimising spacecraft mass and complexity, and atomic oxygen erosion still require further research. Given the scope for significant commercial, societal, and environmental impact which can be realised with higher performing Earth observation platforms, renewed research efforts to address the challenges associated with VLEO operations are required. Highlights: Very low Earth orbit (VLEO) can provide significant benefits over higher altitudes. Higher resolution or lower cost missions can enabled by operating in VLEO. Orbital debris collision risk and radiation damage are also shown to be reduced. Launch vehicle capability is increased and end-of-life deorbit is facilitated.